2009
DOI: 10.1055/s-0029-1185809
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Novel Genes Involved in Artemisinin Production from Flowers ofArtemisia annuaUsing Suppression Subtractive Hybridization and Metabolite Analysis

Abstract: Malaria is a global health problem that threatens 300-500 million people and kills more than one million people annually. Artemisinin is highly effective against multidrug-resistant Plasmodium falciparum and it has been widely used as part of the artemisinin-based combination therapies against malaria. To elucidate the biosynthetic pathway of artemisinin and to clone related genes in Artemisia annua, differentially expressed genes between blooming flowers and flower buds were isolated and characterized by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Although trichome counts have been reported for A. annua, data were obtained only from the adaxial surface of leaves and apparently only from plants in the vegetative phase of growth (Lommen et al, 2006;Liu et al, 2009). Likewise, instead of correlating trichome numbers to their neighboring epidermal cell population, counts have been generally reported as trichomes per unit leaf area and range from 20 to 80 trichomes mm 22 , the number usually declining with leaf maturity (Lommen et al, 2006) although increasing with plant age (Lommen et al, 2006;Liu et al, 2009). Additionally, studies have typically focused on only the adaxial surfaces and the youngest leaves on a given plant, which have the highest density of trichomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although trichome counts have been reported for A. annua, data were obtained only from the adaxial surface of leaves and apparently only from plants in the vegetative phase of growth (Lommen et al, 2006;Liu et al, 2009). Likewise, instead of correlating trichome numbers to their neighboring epidermal cell population, counts have been generally reported as trichomes per unit leaf area and range from 20 to 80 trichomes mm 22 , the number usually declining with leaf maturity (Lommen et al, 2006) although increasing with plant age (Lommen et al, 2006;Liu et al, 2009). Additionally, studies have typically focused on only the adaxial surfaces and the youngest leaves on a given plant, which have the highest density of trichomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent gene expression study in A. annua by Liu et al (2009) used the A. annua 'H050139'. Their work showed little to no change in FPS or CYP levels, whereas our study found large decreases in both transcript levels accompanying the transition from floral bud to full flower.…”
Section: Discussionmentioning
confidence: 99%
“…These transcription factor genes do not directly take part in the artemisinin synthesis pathway but indirectly regulate the artemisinin production. WRKY1 was suggested to regulate the expression of the ADS gene [8] and TTG1 was reported to promote glandular trichome initiation [9]. The expression of TTG1 was up-regulated by COS treatment revealing the possibility of a positive effect of COS on glandular trichome formation.…”
Section: Resultsmentioning
confidence: 99%
“…AaWRKY1: A. annua WRKY transcription factor 1; ADS: amorpha-4,11-diene synthase; CPR: cytochrome P450 reductase; CYP: cytochrome P450 monoxygenase; DBR: artemisinic aldehyde 11 (13) reductase. The genes selected for analysis in this paper were underlined in figure. ENHANCER OF GLABRA3 (GL3), which promote trichome initiation were isolated from an A. annua subtractive cDNA library [9].…”
Section: Introductionmentioning
confidence: 99%
“…AaAS was initially identified from a leaf cDNA library by similarity to known sesquiterpene synthases from plants (Mercke et al, 2000;Wallaart et al, 2001) and its specific pattern of expression in trichomes was later confirmed (Bertea et al, 2005;Olofsson et al, 2011). A succession of oxidation steps requiring a P450 mono-oxygenase (CYP71AV1) and an aldehyde dehydrogenase leads to artemisinic acid, while the synthesis of de-hydro-artemisinic acid requires the intervention of reductase (DBR2) (Zhang et al, 2008;Liu et al, 2009;Teoh et al, 2009;Wang et al, 2009;Zhang et al, 2009;Weathers et al, 2011). Although much progress has been achieved in the elucidation of the artemisinin pathway, relatively little was done with regards to promoter identification.…”
Section: Artemisiamentioning
confidence: 99%